Immersive Virtual Reality and Computational Approaches for Advancing Chemistry Education: A Narrative Review - Hamidon, Noor Fazrieyana; Mohd Zaid, Hayyiratul Fatimah; Jumbri, Khairulazhar (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
This narrative review explores the integration of virtual reality (VR) as a transformative instructional medium in computational chemistry, focusing on how VR can address challenges such as limited 3D visualization and costly experimental setups. VR tools like iMD-VR and Nanome offer immersive interaction with 3D molecular structures, enhancing both conceptual understanding and practical skill development. By fostering engagement, critical thinking, and confidence among learners, VR makes complex chemical phenomena more accessible. However, infrastructure limitations and insufficient empirical data persist, especially in resource-constrained regions. Recent studies emphasize cloud-based solutions and collaborative VR labs to reduce costs and improve scalability. This review highlights VR’s potential to modernize chemistry education, calling for more rigorous research to validate its long-term impact on learning outcomes.